From Aristotle's Teleology to Darwin's Genealogy - Solinas, M. author. aut Link
X, 182 p.
Keywords: From Aristotle to Darwin, from ancient teleology to contemporary genealogies, this book offers an overview of the birth and then persistence of Aristotle's framework into modernity, until its radical overthrow by the evolutionary revolution.